Tailoring periodical collections to meet institutional needs. - Delman, B S (1984)
A system for tailoring journal collections to meet institutional needs is described. The approach is based on the view that reference work and collection development are variant and complementary forms of the same library function; both tasks have as their objective a literature response to information problems. Utilizing the tools and procedures of the reference search in response to a specific collection development problem topic, the author created a model ranked list of relevant journals. Finally, by linking the model to certain operational and environmental factors in three different health care organizations, he tailored the collection to meet the institutions' respective information needs.